(untitled) (Malay Literature, 2024)
Proverbs are literary arts that represent real-life facts and events. The study of the origins of Arabic proverbs in terms of their occasions and narratives is widely available. This is unlike their Malay counterparts, whose origins are often unknown. However, some details of proverbs can be discovered by understanding the meanings of environment-related words within them. For example, a proverb may refer to the people who coined it, the place it came from, or the time it was said. Proverbs often contain narrative elements like prose literary texts, such as novels and stories. However, they differ in that the creators of those texts are specifically known, and their environment is often imaginary. Proverbs, on the other hand, are more akin to a collective product of an entire people, with their environment always rooted in reality, especially Malay proverbs when compared to Arabic ones. Hence, this study aims to investigate the environmental origins of Arabic and Malay proverbs, as well as to analyse the environmental words within both Arab and Malay proverbs through a descriptive comparative approach. The main finding of this study indicates that even if the stories and occasions behind the Malay proverbs are lost, their words indicate that they stay true to the nature of proverbs in general, and this makes their environment clearly authentic and unimaginary. Therefore, each environment has its own words that tell its stories and confirm its authenticity. Full text: PDF